Role of Reporting in Compliance Monitoring and Enforcement of Ballast Water Management - Kaushal E. Mapari; Venkat Krishnamurty; Arga Chandrashekar Anil (Universitas Gadjah Mada, 2018)
The Decision Support System (DSS) for ballast water management in any given port is dependent on the availability of information on ballast water carried by a ship in advance. Collation of information through Ballast Water Reporting Forms (BWRF) has been adopted by several countries. This paper provides a comparison of the reporting forms adopted by some of the countries and the International Maritime Organization (IMO) recommended BWRF. The manually submitted reporting forms have several limitations and India has developed a self-validating Electronic Ballast Water Reporting Form (e-BWRF) to overcome such issues. In addition, the possible direction for reporting in the future is also presented.